Effect of manganese incorporation on the excitonic recombination dynamics in monolayer MoS2 - Chakrabarti, Poulab; Kumar Yadav, Santosh; Deb, Swarup; Dhar, Subhabrata (Journal of applied physics, 2022)
Using x-ray photoelectron spectroscopy, atomic force microscopy, and Raman spectroscopy techniques, we investigate the incorporation of manganese (Mn) in monolayer (1L)- MoS 2 grown on sapphire substrates by microcavity based chemical vapor deposition method. These layers are coated with different amounts of Mn by pulsed laser deposition technique. The study reveals two contrasting Mn-incorporation regimes. Below a threshold deposition amount, thin Mn-coating with large area coverage is found on MoS 2 layers where substitution of Mo ions by Mn is detected through XPS. Dewetting takes place when Mn deposition crosses the critical mark, resulting in the formation of Mn-droplets on MoS 2 layers. In this regime, substitutional incorporation of Mn is suppressed, while the Raman study suggests an enhancement of disorder in the lattice with the Mn deposition time. This knowledge can help us in tackling the challenge of doping of 2D transition metal dichalcogenides in general. From the temperature dependent photoluminescence study, it has been found that, even though Mn deposition enhances the density of non-radiative recombination channels for the excitons, the thermal barrier height for such recombinations to take place also rises. The study attributes these non-radiative transitions to Mo-related defects (Mo-vacancies and/or distorted Mo–S bonds), which are believed to be generated in large numbers during Mn-droplet formation stage.